An Examination of the Likelihood of Home Discharge After General Hospitalizations Among Medicaid Recipients - William N. Mkanta PhD; Neale R. Chumbler PhD; Kai Yang PhD; Romesh Saigal PhD; Mohammad Abdollahi MIE; Maria C. Mejia de Grubb MD, MPH; Emmanuel U. Ezekekwu BPharm (SAGE Publishing, 2017)
Ability to predict discharge destination would be a useful way of optimizing posthospital care. We conducted a cross-sectional, multiple state study of inpatient services to assess the likelihood of home discharges in 2009 among Medicaid enrollees who were discharged following general hospitalizations. Analyses were conducted using hospitalization data from the states of California, Georgia, Michigan, and Mississippi. A total of 33 160 patients were included in the study among which 13 948 (42%) were discharged to their own homes and 19 212 (58%) were discharged to continue with institutional-based treatment. A multiple logistic regression model showed that gender, age, race, and having ambulatory care-sensitive conditions upon admission were significant predictors of home-based discharges. Females were at higher odds of home discharges in the sample (odds ratio [OR] = 1.631; 95% confidence interval [CI], 1.520-1.751), while patients with ambulatory care-sensitive conditions were less likely to get home discharges (OR = 0.739; 95% CI, 0.684-0.798). As the nation engages in the continued effort to improve the effectiveness of the health care system, cost savings are possible if providers and systems of care are able to identify admission factors with greater prospects for in-home services after discharge.